Whiplash.net : estilo de vida e investimento afetivo de fãs no heavy metal brasileiro - Santos, Jefferson Dantas (2014)
This thesis aims to analyze how a site developed, nurtured and consumed by heavy metal fans can have an empowering character. For this, we analyze the Whiplash.net, the most trusted specializing in heavy metal in Portuguese. Theoretically we left assertions of authors like Henri Jenkins, John Fiske, Lawrance Grossberg and Michel de Certeau to show how the action of fans can reverse the logic of consumption prescribed by cultural industries and create new meanings from their everyday life and their interests. Such action is possible due to their affective investment in relation to its object of worship, process which is here understood as active reception process, not only because relativize cultural and media hierarchies, but also generates socialization and conflicts within the lifestyle.